Growth and Productivity of Brachiaria brizantha cv MG 5 under the effect of different dose of NPK fertilization - Umami, N.; Dewi, M. P.; Suhartanto, B.; Noviandi, C. T.; Suseno, N.; Ishigaki, G.; Akashi, R. (2015)
ABSTRACT: This research aimed to investigate the influence of a different dose of NPK fertilization to growth, productivity, and nutrient content of Brachiaria brizantha cv. MG 5. The research was conducted at the Green House of Faculty of Animal Science Universitas Gadjah Mada. Regosols added with manure as basic fertilizer was placed in the poly bag with diameter 25 cm and capacity up to 10 kg. Germination was performed on the poly tray then its results were moved to the poly bag. NPK fertilization was treated on three levels with five replications. The treatment was as follows: given NPK fertilizer level 0 kg ha-1 (P0), 150 kg ha-1(P1) and 300 kg ha-1 (P2), respectively. Fertilization was performed twice during the cultivation period on the 15 and 30 days old. The primary and secondary tillers, the plant’s height, and length were observed once a week in 60 days. Devoliation was performed on the 60th day, with the plants’ height of 10 cm from the soil surface. The variable observed was the plants’ height and length, root biomass production, the ratio of stem and leaves, and dry and organic matter contents. The data was analyzed using analysis of variance. Further, the significantly different result was tested with Duncan’s New Multiple Range Test. The research data showed that the average of the growth of the plants’ length per week for Brachiaria sp age 60 days fertilization level 300 kg/ha resulted the longest plant of 130.7 cm and different (P<0.1) than the others. The number of tillers resulted in no difference, but the biomass production showed that fertilization 150 kg/ha and 300 kg/ha resulted in higher production than 0 kg/ha (P<0.1). The research showed that fertilization 150 kg/ha resulted in higher biomass production than 0 kg/ha, but that of 300 kg/ha did not show a significant difference. Keywords: Brachiaria sp grasses, NPK fertilizer dose, nutrient content, growth, production